Graphene-based nanoarchitecture as a potent cushioning/filler in polymer composites and their applications - Shahnaz T.; Hayder G.; Shah M.A.; Ramli M.Z.; Ismail N.; Hua C.K.; Zahari N.M.; Mardi N.H.; Selamat F.E.; Kabilmiharbi N.; Aziz H.A. (Elsevier Editora Ltda, 2025)
Graphene is a promising candidate for use as a cushioning/filler material in composites due to its extraordinary mechanical and thermal properties. When added to composite materials, graphene can improve the composite's overall strength, durability, and impact resistance. One of the primary benefits of using graphene as a cushioning/filler material in composite materials is its high strength-to-weight ratio. Graphene is one of the most robust materials known to man, and when added to composite materials, it can significantly increase their strength without adding much weight. Another benefit is its high thermal conductivity. Graphene can dissipate heat quickly and efficiently, which can be advantageous in applications where thermal management is critical, such as electronics and aerospace. The addition of graphene can reduce the amount of energy transferred during impact, reducing the risk of damage or failure of the composite material. In addition to its thermal and mechanical properties, graphene is highly chemically resistant, making it ideal for use in harsh environments. It is also relatively inexpensive compared to other high-performance materials, making it an attractive option for large-scale industrial applications. Overall, graphene has the potential to revolutionize the use of composite materials by providing a high-strength, lightweight, and thermally conductive cushioning/filler material that can improve the durability and performance of composite materials in a diverse range of applications. Various application in diverse field has been elaborated in this review work. ? 2023 The Authors